Preliminary December–January inflow and streamflow reconstructions from tree rings for western Tasmania, southeastern Australia. Issue 7 (19th July 2015) - Allen, K. J.; Nichols, S. C.; Evans, R.; Cook, E. R.; Allie, S.; Carson, G.; Ling, F.; Baker, P. J.
Abstract: Projected decreases and changes in the seasonal distribution of precipitation will have profound impacts on southeastern Australia, including its ability to generate renewable hydroelectricity. Recent decreases in precipitation over the region may be significant in the context of instrumental records, but the question of whether these decreases are within long‐term natural variability remains. To help address this issue, we present December–January streamflow and dam inflow reconstructions for southeastern Australia. These reconstructions for the Tasmanian west coast are based solely on local tree ring chronologies and span up to 1600 years. Nonparametric estimates, however, indicate good model skill for the last 458 years (streamflow) and 478 years (dam inflow). The reconstructions indicate that twentieth century conditions were well within the range of historical variability, and were in fact relatively wet. The period from approximately 1600 to 1750 CE was one of the enhanced variability and a high proportion of low and high flow events occurred in the seventeenth century. There are significant relationships between streamflow and inflow reconstructions and large‐scale ocean‐atmosphere processes such as ENSO and the Southern Annular Mode. Critically, our two reconstructions rely heavily on new tree ring chronologies based on properties such as tracheid radial diameter, cell wall thickness, and density, underscoring the importance of these different types of chronologies in reconstructions. Key Points: Multicentennial December–January hydrological reconstructions western Tasmania Twentieth century wetter than average, severe extended dry periods in past Nontraditional tree ring chronologies key to successful reconstructions